Revisiting the Energy-Happiness Paradox: A Quasi-Experimental Evidence of Electricity Access in Indonesia - Nasrudin, Rus’an; Quarina, Qisha; Dartanto, Teguh (Springer Science and Business Media B.V., 2022)
This study revisits the energy-happiness paradox hypothesis using the context of a developing nation. We used Indonesia as a case study, a unique archipelagic country with sparse subnational energy infrastructure, leading to the persistent regional energy access gap. We employed an instrumental variable technique to obviate conventional bias in the happiness regression. The model utilised a newly available national-level household survey on life satisfaction and historical data on digital maps of Indonesia’s electricity infrastructure conditions in 1985. Unlike the phenomena known as the energy-happiness paradox found mainly in the developed countries that suggest the null relationship between having energy access and people’s happiness, our finding reveals a positive effect of electricity access on people’s happiness. We also show that the mechanism in which the effect operates is through individuals’ satisfaction with housing conditions. The heterogeneity analysis shows that the impact of electricity access on happiness is more prominent in the lagging region. It justifies the placed-based policy strategy by the government in developing countries for expanding electricity access in favour of disadvantaged areas. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.